(3GdefJUa ddSGQb hGdeSQhb efg (B((3aj EXgGQ SQbGJ CHj GdWjH GdeJfHi(B)s - (3CHi eMeO GdMSf Hf Ydj GdVHi GdeYQha HGHf hcjY GdJfjSis; (3CHhGdWjH CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO Hf GdLYaj Gdchaj GdeYQha H` CHj GdWjH GdoeJfHj,J (B354 (3g` s ((3eSYhO Hf YHGS Hf Ydi Hf CHj YeQh s)
(3ChdgG (B:s
(3GeG HYO MeO Gddg aEfg hUd Edi cJGHc GdLdjd GdehVY, GddWja GdehbY s
(3BNQgG (B:s
(3EPG JQMdJ Yf bhe hbO bOQhG Cf dG JaGQbge aGdQGMdhf ge gPG eG hLO ef GdfSNI s
(3HgG bdjd ef GdJbWjY hGdJQbjY WeSG GdcJGHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B115 s
Keywords: (3GdCOHs